Sensory evaluation of wine through correspondence analysis: a theoretical and empirical rationale - Magalios, Panayiotis; Kosmas, Petros C.; Tsakiris, Argiris; Theocharous, Antonis L. (My University, 2019)
Sensory evaluation in wine research focuses on understanding wine preference and choice within a holistic framework. This study offers a theoretical and empirical rationale for the sensory evaluation of wine. A precondition for sustainability and success in the market arena is a clear understanding of potential interaction of sensory evaluation properties and other factors affecting consumer choice. New approaches and methodologies for preference matching and assessment of sensory properties and information queues on overall liking are of fundamental importance for wine makers. The aim of this study is to advance the understanding of sensory evaluations affecting consumer both on empirical and theoretical grounds. For the implementation of this aim, an empirical research with real wine tasting data was conducted and analyzed through the use of Correspondence Analysis (CA). The findings of this study demonstrate that this method is more appropriate in wine sensory data analysis due to their categorical and non-parametric nature. CA is a very useful technique to establish a solid knowledge for the identification of the wines based on evidence and facts of their aromatic characteristics.
Keywords: Correspondence analysis; Sensory evaluation; Wine research